A method for the hazard assessment of regional geological disasters: a case study of the Panxi area, China. Issue 1 (2nd January 2021) - Lai, Fang; Shao, Qiufang; Lin, Ying; Yi, Xia; Sun, Xiaofei; Shao, Huaiyong; Xian, Wei; Peng, Peihao
ABSTRACT: A novel geological hazard assessment model was developed by integrating an analytic hierarchy process (AHP) and a projection pursuit model (PPM) in this study. Remote sensing (RS) and geographic information system (GIS) techniques were also coupled and the hazard risk of the Panxi area in western China was assessed to test the model feasibility. The results show the model coupled with the GIS technique not only enables regional geological hazard risk assessment but also quantitatively visualizes its spatial distribution; and the model is ideally suitable for regional geological hazard risk assessment because it fully considers the subjective and objective factors.